E-DIPLOMACY AND POLITICAL NARRATIVES (A CASE STUDY OF US PRESIDENTIAL ELECTIONS 2024) (Contemporary Journal of Social Science Review, 2025)
This study investigates about the E diplomacy and the global political narratives and its impact on the local political outcomes through the case study of 2024 US presidential elections and how it has influenced the Pakistani political scenario. E diplomacy also known as digital diplomacy with the platforms like X formerly known as Twitter, Facebook and YouTube used by the state leaders, diplomats and international actors but it has remained mostly underexplored. This research fills the critical gap by finding in depth that how global narratives shape the local diplomacy and human rights in context of US general election 2024 and how the Pakistan domestic political environment changed after it, the study employees agenda setting and framing theory and analyses the strategic communication via E platforms which has influenced the public opinions and the political discourse. The study also investigates about the Indo-Pak War (May 2025) and the social media factor of E-diplomacy. The findings contribute to the field of political communication, foreign policy, international relations, diplomacy and the digital media. The study highlights Bi-directional influence of digital and E diplomacy through global political events and its impact on local political scenarios in digitally interconnected world.